Early Factors Associated with the Development of Chronic Pain in Trauma Patients - Raoul Daoust; Jean Paquet; Lynne Moore; Marcel Émond; Sophie Gosselin; Gilles Lavigne; Manon Choinière; Aline Boulanger; Jean-Marc Mac-Thiong; Jean-Marc Chauny (Pain Research and Management, 2018)
Objective. To identify factors, available at the time of trauma admission, associated with the development of chronic pain to allow testing of preventive approaches. Methods. In a retrospective observational cohort study, we included all patients ≥ 18 years old admitted for injury in 57 adult trauma centers in the province of Quebec (Canada) between 2004 and 2014. Chronic pain was defined as follows: treated in a chronic pain clinic, diagnosed with chronic pain, or received at least 2 prescriptions of chronic pain medications 3 to 12 months postinjury. Results. A total of 95,134 patients were retained for analysis. Mean age was 59.8 years (±21.7), and 52% were men. The causes of trauma were falls (63%) and motor vehicle accidents (22%). We identified 14,518 patients (15.3%; 95% CI: 15.1–15.5) who developed chronic pain. After controlling for confounding factors, the variables associated with chronic pain were spinal cord injury (OR = 3.9; 95% CI: 3.4–4.6), disc-vertebra trauma (OR = 1.6; 95% CI: 1.5–1.7), history of alcoholism (OR = 1.4; 95% CI: 1.2–1.7), history of anxiety (OR = 1.4; 95% CI: 1.2–1.5), history of depression (OR = 1.3; 95% CI: 1.1–1.4), and being female (OR = 1.3; 95% CI: 1.2–1.3). The area under the receiving operating characteristic curve derived from the model was 0.80. Conclusions. We identified risk factors present on hospital admission that can predict trauma patients who will develop chronic pain. These factors should be prospectively validated.